Electrochemistry Investigation on the Graphene/Electrolyte Interface. Issue 12 (15th July 2015) - Du, Xiaowei; Guo, Hui; Jin, Yan; Jin, Qinghui; Zhao, Jianlong
Abstract: In this study, the graphene/electrolyte interface was investigated in detail by the electrochemical method. The total interface capacitance was calculated from the electrochemical impedance spectroscopy (EIS) results, and its responses to different concentrations and pHs were also investigated. The minimum point of the capacitance was found to shift to right (vs. Ag/AgCl) as the concentration increased, and to left with increasing pH. As a comparison, gold/electrolyte interface was investigated in the same way, but didn't show the similar behavior. To further explore the interface capacitance, proper models were proposed to fit the EIS results. Two constant‐phase elements (CPE) were used in the graphene‐electrolyte interface model to represent the double‐layer capacitance (CPEdl ) and the quantum capacitance (CPEq ), respectively. The CPEq exhibited its sensitivity to concentration and pH, while CPEdl did not. This study gives a new aspect to detect concentration and pH, and may provide a reference for the graphene‐based supercapacitor research. Abstract :